Kajian Sistem Penghawaan terhadap Kenyamanan Termal pada Rumah Produksi Tenun Bukan Mesin - Astrihasna Shafa; Gagoek Hardiman; Wahyu Setia Budi (Universitas Sebelas Maret Surakarta, 2023)
Thermal comfort is essential when designing a building that will serve as a work activities place. A comfortable work environment will increase worker productivity. This study is a form of correction to non-machine weaving production house to obtain an optimal ventilation system for achieving thermal comfort. This research uses quantitative in non-machine weaving production house in Pekalongan. The data collected are thermal measurement data and air intensity in the workspace directly from morning to evening for two days. Measurements using a thermometer, hygrometer, and hot wire anemometer. Measurements were carried out in two conditions to compare the air intensity in the workspace. The measurement results will be analyzed using the recommended standards. The observations show that natural ventilation is not optimal in a horizontal building and an open space with an inner court. The fan's type and shape affect the airflow arrangement in the room.